The relationship between discriminatory work environment and psychological distress in Italian organizations: Are lack of supervisor support and economic stress mediating factors? - Giorgia BONDANINI; Gabriele GIORGI; Francesco CHIRICO; Amelia RIZZO; Hicham KHABBACHE; Francesca ROMANA TESTA; Giulia FOTI; Federico ALESSIO; Valerio VINCIARELLI; Georgia Libera FINSTAD (Journal of Health and Social Sciences)
Introduction:The construct of a discriminatory work environment is becoming increasingly significant in organizations due to its potential impact on corporate, health, and economic stress. Economic stress, in particular, can be viewed as a potential stressor, comprising both objective and subjective components. This research aims to demonstrate how the perception of a discriminatory work environment can affect workers’ perceived well-being, considering supervisor support and economic stress as potential mediators. Methods:A parallel mediation analysis was conducted on 170 managers to examine the associations between a discriminatory work environment, psychological distress, supervisor support, and economic stress. Subsequently, a simple mediation model was tested on a second sample of 358 employees to explore the relationships between a discriminatory work environment, supervisor support, and psychological distress. Results:The findings indicate that the total effect of a discriminatory work environment on employees’ psychological well-being is significant. Additionally, there is a direct positive effect of a discriminatory work environment on employees’ psychological distress, supervisor support, and economic stress. In the second sample, the results demonstrate that a discriminatory work environment significantly affects the lack of supervisor support, which, in turn, significantly impacts psychological distress. Discussion:This research highlights the importance of promoting a non-discriminatory work environment to ensure greater psychological well-being and foster a positive organizational climate. Assessing and training managers to provide effective support may also be promising strategies for enhancing well-being and performance in the workplace.